2011
DOI: 10.1249/mss.0b013e31821d3f6f
|View full text |Cite
|
Sign up to set email alerts
|

Estimating V˙O2peak from a Nonexercise Prediction Model

Abstract: The nonexercise regression model developed in the present study was fairly accurate in predicting V·O 2peak in this healthy population of men and women. The model might be generalized to other healthy populations and might be a valid tool for a rough assessment of cardiorespiratory fitness in an outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
221
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(244 citation statements)
references
References 29 publications
11
221
2
10
Order By: Relevance
“…Also in a study by Ainsworth et al (1992) [2] age, gender, BMI and frequency of vigorous exercise per week explain 75% of the variations in VO 2 max for men. Recently, Nes et al (2011) [22] have further demonstrated that age, waist circumference, leisure time physical activity and resting heart rate together explained 61% of variance in VO 2 max for men.…”
Section: Discussionmentioning
confidence: 97%
“…Also in a study by Ainsworth et al (1992) [2] age, gender, BMI and frequency of vigorous exercise per week explain 75% of the variations in VO 2 max for men. Recently, Nes et al (2011) [22] have further demonstrated that age, waist circumference, leisure time physical activity and resting heart rate together explained 61% of variance in VO 2 max for men.…”
Section: Discussionmentioning
confidence: 97%
“…One systematic review 171 of 13 nonexercise equations is presented in Table 6. 172,[179][180][181][182][183][184][185][186][187][188][189][190] These equations were developed with cross-sectional data using age, sex, body weight (or body mass index, percentage of body fat, waist circumference), physical activity/exercise/ training (self-reported or measured), smoking, resting HR, or perceived functional ability as predictors of CRF. The R 2 and SEEs ranged from 0.50 to 0.86 and 2.98 to 6.90 mL·kg…”
Section: Submaximal Exercise Testing Without Cpx Measurementsmentioning
confidence: 99%
“…172,174,181,191 A limitation of these equations is that they tend to underestimate and overestimate CRF at the upper and lower ends of the distribution, respectively. 172,179,180,182,185,190 The underestimation is unlikely to affect highly fit individuals, who will still be correctly classified into the higher CRF categories; however, the overestimation for people with low CRF could be a concern because of the associated heightened risk among these men and women. 38,172,182,192 Despite this, most models derived from large studies correctly classify individuals into low-fitness categories.…”
Section: Submaximal Exercise Testing Without Cpx Measurementsmentioning
confidence: 99%
See 2 more Smart Citations